Rhinolith: An Incidental Finding in a Patient Under Orthodontic Treatment - Momeni , Amirali; Moshfeghi, Mahkameh; Alizad, Maryam (Journal of Dental School, 2022)
Objectives Rhinolith is an uncommon condition that results from calcification of an endogenous or exogenous nidus within the nasal cavity. It may present asymptomatically or cause symptoms like headache and nasal obstruction. Case: In this case report, we present a case of an unusual and quite big rhinolith in a 17-year-old male which was undetected for some time, and was accidentally found in the radiographic examination. It possibly originated from a retained foreign body in childhood. We discuss its clinical and radiographic features and its effect on the surrounding structures. Conclusion Radiographic assessment and rigid endoscopy are important to evaluate the rhinolith’s location.